Preparation and characterization of a novel triple composite scaffold containing silk fibroin, chitosan, extracellular matrix and the mechanism of Akt/FoxO signaling pathway in colonic cancer cells cultured in 3D - Cao, Zhipeng; Chen, Liang; Niu, Gengming; Li, Yan; Hu, Zhiqing; Hong, Runqi; Zhang, Xiaotian; Hong, Liang; Han, Shanliang; Ke, Chongwei (Frontiers in Bioengineering and Biotechnology, 2023)
This work examined the Physical and chemical properties properties and biocompatibility in vivo and in vitro of an unique triple composite scaffold incorporating silk fibroin, chitosan, and extracellular matrix. The materials were blended, cross-linked, and freeze-dried to create a composite scaffold of silk fibroin/chitosan/colon extracellular matrix (SF/CTS/CEM) with varying CEM contents. The SF/CTS/CEM (1:1:1) scaffold demonstrated the preferable shape, most outstangding porosity, favourable connectivity, good moisture absorption, and acceptable and controlled swelling and degradation properties. Additionally, HCT-116 cells cultivated with SF/CTS/CEM (1:1:1) showed exxcellent proliferation capacity, cell malignancy, and delayed apoptosis, according to the in vitro cytocompatibility examination. We also examined PI3K/PDK1/AKT/FoxO signaling pathway and discovered that the scaffold culture of SF/CTS/CEM (1:1:1) may prevent cell death by phosphorylating Akt and suppressing FoxO expression.Our findings demonstrate the potential of the SF/CTS/CEM (1:1:1) scaffold as an experimental model for colonic cancer cell culture and for replicating the three-dimensional in vivo cell growth environment.